PENGENALAN KLENTENG CU AN KIONG SEBAGAI DESTINASI WISATA DI REMBANG, JAWA TENGAH - Haryanto, Eko; Angelia, Ernitha (Kepariwisataan: Jurnal Ilmiah, 2016)
Rembang is a regency in Central Java province, has 14 districts one of which is the District Lasem. Cu An Kiong temple is the oldest temple in Central Java, which has a wealth of cultural, historical stories, art, and has great potential as a tourist destination mainstay in Rembang, Central Java. This study aims to introduce Cu An Kiong temple as a cultural tourism destination other than Kartini Museum and shopping at batik Lasem better known and visited by tourists. The role of government introduced Cu An Kiong temple as a tourist destination in Rembang are still not maximum and effective. This study used a qualitative descriptive and SWOT analysis The study also focused on the potential for Cu An Kiong temple that is worth a visit by tourists. Results from this study is that the Cu An Kiong temple can be recognized as one of the tourist destinations worth visiting in Rembang. Keywords: cultural tourism, Destination Tourism, visitors